Equilibrium Selection in Auctions and High Stakes Games - Milgrom, Paul; Mollner, Joshua (Econometrica, 2018)
We introduce the testâ€ set equilibrium refinement of Nash equilibrium to formalize the idea that players contemplate only deviations from equilibrium play in which a single competitor plays a nonâ€ equilibrium best response. We then apply this refinement to three wellâ€ known auction games, comparing our findings to similar ones previously obtained by specialized equilibrium selections. We also introduce a theory of high stakes versions of games, in which strategies are first proposed and then subjected to a potentially costly reviewâ€ andâ€ revise process. We demonstrate a sense in which the testâ€ set equilibria emerge from such processes when the cost of revision is small.